Identification of Bird Species in Argowiloso Peak Mount Muria - Ridlo, Muhammad; Setyawati, Siti Mukhlishoh; Hidayat, Saifullah (Al-Hayat: Journal of Biology and Applied Biology, 2022)
AbstractIndonesia is a country that has abundant flora and fauna. Mount Muria, Kudus Regency, Central Java has a high potential for bird biodiversity. The area which is a natural protected forest area, is very supportive for the existing bird habitat. However, this potential is still rarely known by the general public due to the lack of publications. The aims to find out and analyze the types of birds and to find out and analyze the condition of the bird habitat found in the Mount Muria area. The research was conducted using the transect method with 3 observation stations. The observed birds were then photographed and identified based on the field guide of MacKinnon. The results showed that 22 species 18 families were identified, including: Campephagidae, Vangidae, Sittidae, Pycnonotidae, Rhipiduridae, Nectariniidae, Eurylaimidae, Pellorneidae, Hirundinidae, Cisticolidae, Dicaeidae, Pittidae, Alcedinidae, Meropidae, Megalaimidae, Apodidae, Accipitridae and Cuculidae. Habitat conditions are strongly influenced by biotic and abiotic components to support the survival and diversity of birds on Mount Muria